47CRT-D versus CRT-P: are we on the right track?. (18th June 2020) - Stassen, J; Scherrenberg, M; Vijgen, J; Dilling, D; Herbots, L; Timmermans, PH J; Schurmans, J; Verwerft, J; Koopman, P
Abstract: Introduction: Implantable cardioverter defibrillators (ICD) and cardiac resynchronisation therapy (CRT) have both proven to reduce mortality in patients with heart failure (HF). However, randomised trials comparing CRT-pacemaker (CRT-P) vs CRT-defibrillator (CRT-D) are lacking. Understanding a patient's primary mode of death is therefore important as this may guide the proper use of CRT systems and avoid risks that are associated with under -or overtreatment with an ICD. Purpose This study aims to analyse the mode of death and the occurrence of life-threatening ventricular arrhythmias (VAs) in patients who received a CRT-P or CRT-D. This may help in the future selection for an appropriate cardiac device in patients with HF. Methods Patients with HF undergoing CRT-P or CRT-D implantation in a tertiary hospital between January 2008 and December 2018 were retrospectively evaluated. CRT indications were in compliance with the ESC guidelines. The decision to implant CRT-D or CRT-P in primary prevention was left at the discretion of the treating physician but was based on ESC clinical guidance. Life threatening VAs (sustained ventricular tachycardia > 30s not requiring therapy or appropriate therapy for VAs) and mode of death were analysed. Results 511 patients were implanted with a CRT (CRT-D/CRT-P; n = 311/200) of which 410 (CRT-D/CRT-P; n= 245/165) were followed in our centre for 63, 5 ± 38, 1 months. Patients with CRT-P were older (77, 6 ± 8, 1 vs 66, 8 ± 9, 5 years; p <0, 001), more often female (39, 4 vs 26, 9%; p 0, 006), had more a non-ischaemic cause (61, 2 vs 44, 9%; p 0, 001) and a significant higher comorbidity burden. They also received less treatment with neurohumoral blockers. Baseline LVEF was higher in the CRT-P group (33, 1 ± 8, 9 vs 28, 0 ± 7, 6%, p <0, 001). 6 months follow-up showed a similar increase in LVEF in the CRT-P vs CRT-D group (+10, 3 ± 9, 6 vs +11, 4 ± 10, 8%, p 0, 38). Main reasons to choose for CRT-P were RV-pacing induced cardiomyopathy (CMP) (26, 1%), multiple comorbidities (18, 8%), HF complicated by high degree AV block or AV junction ablation (18, 2%), non-ischaemic CMP with suspected good CRT response (10, 3%), age (7, 3%), other (19, 3%). 6/165 patients with CRT-P (3, 6%), of which 5 were detected by remoted telemonitoring, vs 51/245 with CRT-D (20, 8%) experienced episodes of life-threatening arrhythmias (p <0, 001). All-cause mortality was higher in the CRT-P vs CRT-D group (36, 4 vs 25, 3%, p 0, 005). However, the CRT-P group had a predominant non-cardiac mode of death (70, 9 vs 43, 3%, p <0, 001). Death secondary to a tachyarrhythmic event was present in only 1 patient (1, 7%) in the CRT-P group. Conclusions: Guided by clinical parameters and presence of competitive non-cardiac causes of death, adequate decision between CRT-P or CRT-D implantation can be made. In our cohort, sudden cardiac death in the CRT-P group occurred only once. Remote monitoring is able to identify a subgroup of patients potentially benefiting from an upgrade from CRT-P to CRT-D.